دور الوالي في الحفاظ على الصحة العامة خلال جائحة كورونا The wali’s role in maintaining public health during COVID-19 pandemic - واصلي محمد; عباس راضية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الورقة إلى دراسة دور الوالي في الحفاظ على الصحة العامة خلال تفشي جائحة كورونا كوفيد19، الذي يهدد هذه الأخيرة التي تعتبر إحدى الركائز الثلاث للنظام العام التي تسعى هيئات الضبط الإداري لحمايتها، وباعتبار أن الوالي احد هذه الهيئات على المستوى المحلي، فقد منحت له من خلال القوانين التي صدرت في هذا الإطار، صلاحيات واسعة وزود بوسائل مختلفة تمكنه من اتخاذ مختلف الإجراءات والتدابير التي من شئنها المحافظة على الصحة العامة في ظل تفشي هذا الوباء، وقد اعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي. ومن أهم النتائج التي خلصنا إليها أن ظهور جائحة كورونا كوفيد19، كان سبب في استصدار نصوص قانونية جديدة وسعت من صلاحيات الوالي بهدف الحفاظ على الصحة العامة. Abstract: This research paper aims to study the role of the Wali in preserving public health during the outbreak of the COVID-19 pandemic, which has become a threaten her, one of the three pillars of public order that administrative control agencies seek to protect. Considering that the guardian is one of these bodies at the local level, it has been granted through the laws enacted in this context, A wide range of powers have been provided and various means have enabled him to take various actions and measures such as the preservation of public health in the context of the epidemic In this study, we have relied on the analytical descriptive approach. One of our most important findings is that the emergence of the COVID-19 pandemic was the reason for the issuance of new legal texts that expanded the powers of the wali to preserve public health.